Competition between gelation and crystallisation of a peculiar multicomponent liquid system based on ammonium salts - Kapoor, Iti; Schoen, Eva-Maria; Bachl, Jurgen; Kuehbeck, Dennis; Cativiela, Carlos; Saha, Subhadeep; Banerjee, Rahul; Roelens, Stefano; Juan Marrero-Tellado, Jose; Diaz, David Diaz (Soft Matter, 2012)
An exemplar competition between gelation and crystallisation phenomena was examined with an unusual synergistic multicomponent (organo) gelator solution (MGS), which consists of a well-defined methanolic solution of (1R, 2R)-1,2-diaminocyclohexane L-tartrate containing 2.4 equiv. of concentrated hydrochloric acid. The optimal composition of the MGS was determined through meticulous solubility, gelation and structural studies, which support a transient gelation mechanism based on the kinetic self-assembly of the tartrate salt driven by hydrogen-bonding interactions, involving ammonium nitrogen donors and hydroxyl oxygen acceptors, and electrostatic interactions. The hydrochloric acid is involved in the solubilisation of the salt through an ionic dissociation-exchange process, which ends up with the formation-precipitation of (1R, 2R)-1,2-diaminocyclohexane dihydrochloride. As a consequence, an irreversible destruction of the gel takes place, which indicates the metastable nature of this phase that cannot be accessed from the thermodynamically equilibrated state. Gelation of a variety of oxygenated and nitrogenated solvents with moderate polarity occurred efficiently using extremely low MGS concentrations at low temperatures, and the gel phase was confirmed by dynamic rheological measurements. Several features make the described MGS unique: (1) it is a multicomponent solution where each component and its stoichiometry play a key role in the reproducible formation and stabilization of the gels; (2) it is formed by simple, small, and commercially available chiral building blocks (dissolved in a well-defined solvent system), which are easily amenable for further modifications; (3) the gelation phenomenon takes place efficiently at low temperature upon warming up the isotropic solution, conversely to the typical gel preparation protocol; and (4) the formed organogels are not thermoreversible despite the non-covalent interactions that characterize the 3D-network.

C-C Bond formation catalyzed by natural gelatin and collagen proteins - Kuehbeck, Dennis; Dhar, Basab Bijayi; Schoen, Eva-Maria; Cativiela, Carlos; Gotor-Fernandez, Vicente; Diaz, David Diaz (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C-C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C-C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon-carbon bond formation; gelatin; Henry reaction; protein

Organophotocatalysis in nanostructured soft gel materials as tunable reaction vessels: comparison with homogeneous and micellar solutions - Bachl, Jurgen; Hohenleutner, Andreas; Dhar, Basab Bijayi; Cativiela, Carlos; Maitra, Uday; Koenig, Burkhard; Diaz, David Diaz (Journal of Materials Chemistry A, 2013)
Riboflavin tetraacetate-catalyzed aerobic photooxidation of 1-(4-methoxyphenyl)ethanol was investigated as a model reaction under blue visible light in different soft gel materials, aiming to establish their potential as reaction vessels for photochemical transformations. Three strategies involving different degrees of organization of the catalyst within the gel network were explored, and the results compared to those obtained in homogeneous and micellar solutions. In general, physical entrapment of both the catalyst and the substrate under optimized concentrations into several hydrogel matrices (including low-molecular-weight and biopolymer-based gels) allowed the photooxidation with conversions between 55 and 100% within 120 min (TOF similar to 0.045-0.08 min(-1); k(obs) similar to 0.011-0.028 min(-1)), albeit with first-order rates ca. 1-3-fold lower than in solution under comparable non-stirred conditions. Remarkably, the organogel made of a cyclohexane-based bisamide gelator in CH3CN not only prevented the photodegradation of the catalyst but also afforded full conversion in less than 60 min (TOF similar to 0.167 min(-1); k(obs) similar to 0.073 min(-1)) without the need of additional proton transfer mediators (e. g., thiourea) as it occurs in CH3CN solutions. In general, the gelators could be recycled without detriment to their gelation ability and reaction rates. Moreover, kinetics could be fine-tuned according to the characteristics of the gel media. For instance, entangled fibrillar networks with relatively high mechanical strength were usually associated with lower reaction rates, whereas wrinkled laminated morphologies seemed to favor the reaction. In addition, the kinetics results showed in most cases a good correlation with the aeration efficiency of the gel media.

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry